Manajemen arus kas, ukuran perusahaan, leverage, tahun anomali covid-19 serta kinerja keuangan perusahaan sektor kesehatan di bursa efek indonesia - Ferli, Ossi; Haryanti, Enny; Fadlillah, Robby Adam; Rahman, Rozinur (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This research aims to analyze the impact of Cash Flow Management (CFO), Firm Size, Leverage, and the Anomalous Year of COVID-19 on the financial performance (ROE) of health sector companies listed on the Indonesia Stock Exchange during the period 2017-2022. Panel regression method is employed to test hypotheses and analyze these variables. The results reveal that Leverage has a significant negative influence, while Size has a significant positive effect on financial performance. The Anomalous Year of COVID-19 also demonstrates a positive impact on ROE, indicating adaptation and growth within the health sector during the pandemic. Cash flow management (CFO), though not statistically significant, highlights the complexity of the relationship between operational cash flow and financial performance. These findings provide valuable insights for health sector companies in crafting adaptive and sustainable strategies amidst economic dynamics and specific situations such as a pandemic.